Drug Repurposing Approach Identifies Inhibitors of the Prototypic Viral Transcription Factor IE2 that Block Human Cytomegalovirus Replication. Issue 3 (17th March 2016) - Mercorelli, Beatrice; Luganini, Anna; Nannetti, Giulio; Tabarrini, Oriana; Palù, Giorgio; Gribaudo, Giorgio; Loregian, Arianna
Summary: New targets for antiviral strategies are needed against human cytomegalovirus (HCMV), a major human pathogen. A cell-based screen aimed at finding inhibitors of the viral transcription factor Immediate-Early 2 (IE2) was performed in HCMV-infected cells expressing EGFP under the control of an IE2-inducible viral promoter. Screening of a library of bioactive small molecules led to the identification of several compounds able to inhibit EGFP expression and also HCMV replication with potency in the low-micromolar range. Follow-up studies with four selected hits indicated that they all block viral DNA synthesis as well as viral Early and Late gene expression. Furthermore, mechanistic studies confirmed that the compounds specifically act via inhibition of IE2 transactivating activity, thus blocking viral Early gene expression and the progression of virus replication. These results provide proof of concept for identifying small molecules that modulate the activity of a microbial transcription factor to control pathogen replication. Graphical Abstract: Highlights: A cell-based assay was developed and validated for screening inhibitors of HCMV IE2 Discovery of new inhibitors of HCMV replication in the low-micromolar range Follow-up studies reveal inhibition of viral DNA synthesis and of HCMV E and L genes Inhibition of IE2 transactivating properties identified by mechanistic studies Abstract : Mercorelli et al. describe an approach for identifying inhibitors of the viral transcription factor IE2, which plays a major role in HCMV replication, by using a fluorescence-based cellular assay. This yields to small molecules that could be repurposed as anti-HCMV drugs.